RISK ANALYSIS OF WORK ACCIDENTS IN CONTAINER LOADING AND UNLOADING WORK WITH THE JOB SAFETY ANALYSIS METHOD (SENSISTEK:Riset Sains dan Teknologi Kelautan, 2023)
An activity at a container port  is  not without risk, usually operating lifting and transportation support equipment in the form  of rubber tyre gantry crane (RTG) or  loading container crane (CC). In loading and unloading is one of the big causes of work accidents. One way to control potential risks and hazards is first by analyzing the possibility of work accidents using Job Safety Analysis (JSA) to minimize the possibility of work accidents during the loading and unloading process. This study aims to analyze the  potential hazards and risks arising in each container handling activity, using JSA analysis and identifying actions or procedures to control potential hazards and risks that will arise at each stage of work. The advantage of this research is that it can be used as a basis and information in the form of hazards and risks of work accidents and to conduct occupational safety analysis such as assessment of the risk of work accidents in this field. The process of loading and unloading containers is a reference in controlling the risk of accidents in the workplace, especially during handling or haulage activities. The analysis process is carried out after, the process of identifying potential hazards is carried out. Risk assessment is a process of prioritizing the control of the risk level of accidents or occupational diseases, so as to reduce the increased risk of accidents in the loading and unloading process